The effects of physical exercise on soluble transferrin receptor and other indicators of iron status in female taekwondoist - Rahmani-Nia, F.; Rahnama, N.; Masoumi, S. (International Journal of Sports Science and Engineering, 2007)
Iron and iron-binding proteins play a significant function in the physiology of various human systems. The aim of this study was to evaluate the effect of two different types of physical activity on soluble transferrin receptor concentration and other indicators of iron status in female taekwondoist. Thirteen members of the National Taekwondo team aged 18-25 yrs with about 4.5 yrs training experience participated in this study. Body mass and height of subjects were accordingly 57.5 ± 13.7 kg and 168.3 ±7.1 cm. They performed two different laboratory tests: A, incremental treadmill running test and B, 30 - min running test at constant speed at 50% of the HR max. The interval between the tests was 5 - days and the subjects were instructed to refrain from strenuous physical exercise for 2 - days before test - A and throughout interval test A and B. Blood sample was withdrawn 20 - min before and immediately after two types of tests and were analyzed iron, ferritin, transferrin, sTfR, hemoglobin and hematocrit. Data were analyzed by student t -test. Our results showed that hematocrit increased significantly (P < 0.05) after test A, but not in test B. Soluble transferrin receptor increased after tests A and B, but increases were significant (P < 0.05) after test A only. Also, iron decreased significantly (P < 0.05) after test A and B. However, there were not significant differences (P > 0.05) in ferritin, transferrin receptor and hemoglobin after exercise. It can be concluded that variable of the iron status responded to physical stress and erythropoietic activity and if iron deficiency do not compensate, athletes may experience anemia.